Independent evolution of pouched flowers in the Amazon is supported by the discovery of a new species of Lesia (Gesneriaceae) from Serra do Aracá tepui in Brazil - Ferreira, Gabriel Emiliano; Chautems, Alain; Hopkins, Michael John Gilbert; Perret, Mathieu (Plant Systematics and Evolution, 2016)
We describe and illustrate Lesia tepuiensis, a new species of subshrub from rock outcrops of the Serra do Aracá tepui in Amazonas, Brazil. Phylogenetic analyses based on 7219-aligned base pairs of the plastid and nuclear DNA sequences recovered the new species as sister to Lesia savannarum, the type species of Lesia, a genus recently described as monotypic. The new species is readily distinguished from L. savannarum by having a red, pouched corolla tube, lanceolate calyx lobes, a hirsute to tomentose leaf indument and a rupicolous habit. Phylogenetic analyses of the relationships of Lesia with other genera in the subtribe Columneinae indicated that Lesia and Codonanthopsis form a monophyletic group sister to a clade endemic to the Brazilian Atlantic forest formed by Nematanthus and Codonanthe. The pouched corolla tube found in the genera Lesia and Nematanthus appears to have evolved independently in these two lineages. Ecological and distributional data, as well as a key to the species of Lesia and related genera, are also provided. © 2016, Springer-Verlag Wien.